Progress in Myrtaceae genetics and genomics: Eucalyptus as the pivotal genus - Grattapaglia, Dario; Vaillancourt, René E; Shepherd, Merv; Thumma, Bala R; Foley, William; Külheim, Carsten; Potts, Brad M; Myburg, Alexander A (Tree genetics & genomes, 2012)
The status of genomics and genetics research in the Myrtaceae, a large family of dicotyledonous woody plants, is reviewed with Eucalyptus as the focal genus. The family contains over 5,650 species in 130 to 150 genera, predominantly of neo-tropical and Southern Hemisphere distribution. Several genera are well known for their economic importance worldwide. Myrtaceae are typically diploids with small to intermediate genome size. Microsatellites have been developed for several genera while higher throughput marker systems such as diversity arrays technology and single nucleotide polymorphism are available for Eucalyptus. Molecular data have been fundamental to current perspectives on the phylogeny, phylogeography and taxonomy of the Myrtaceae, while numerous studies of genetic diversity have been carried out particularly as it relates to endangered, rare, fragmented, overharvested or economically important species. Large expressed sequence tag collections for species of Eucalyptus have recently become public to support the annotation of the Eucalyptus grandis genome. Transcriptomics in Eucalyptus has advanced by microarrays and next-generation sequencing focusing on wood development. Linkage maps for Eucalyptus display high synteny across species and have been extensively used to map quantitative trait loci for a number of traits including growth, wood quality, disease and insect resistance. Candidate gene-based association genetics have successfully found marker–trait associations for wood and fiber traits. Genomic selection experiments have demonstrated clear potential to improve the efficiency of breeding programs while freeze-tolerant transgenic Eucalyptus trials have recently been initiated. The recently released E. grandis genome, sequenced to an average coverage of 8×, will open up exceptional opportunities to advance Myrtaceae genetics and genomics research.